Cross Talk Between Ferroptosis and Cerebral Ischemia - She, Xu; Lan, Bin; Tian, Haomei; Tang, Biao (Frontiers in Neuroscience, 2020)
Recently, ferroptosis has been revealed as a new form of regulated cell death. Distinct from apoptosis and necrosis, ferroptosis is evoked by iron-dependent lipid peroxidation. Furthermore, the metabolism of iron, lipids, and amino acids plays a significant regulatory role in ferroptosis, which can be reversed by glutathione peroxidase 4 and ferroptosis suppressor protein 1. Ferroptosis is implicated in the onset and development of numerous neurological diseases. Emerging studies have reported that ferroptosis induces and aggravates brain tissue damage following cerebral ischemia, whereas inhibition of ferroptosis dramatically attenuates induced damage. In this review, we have summarized the mechanistic relationship between ferroptosis and cerebral ischemia, including through iron overload, downregulation of glutathione peroxidase 4, and upregulation of lipid peroxidation. Although considerable attention has been paid to the effect of ferroptosis on cerebral ischemic injury, specific mechanisms need to be experimentally confirmed, including how cerebral ischemia induces ferroptosis and how ferroptosis deteriorates cerebral ischemia.